“Soft power” of India: the role of culture in globalization processes - Kenbayev, Sh.; Parikh, Margie (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2025)
The article is devoted to the analysis of the concept of "soft power" in the context of the foreign policy strategy of India. The paper examines important aspects of cultural diplomacy, religious and philosophical heritage, the influence of cinema, culinary traditions, and the role of the Indian diaspora as a means of transnational influence. The author emphasizes that the "soft power" of India is formed not only as an element of cultural expression but also as a purposeful political and diplomatic resource, which is actively used to form a positive image of the country in the international arena. The historical development of Indian "soft power", from Mahatma Gandhi’s nonviolent policies to the Indian national movement and modern initiatives led by Prime Minister Narendra Modi, has been highlighted. It is noted that India consciously uses cultural and spiritual heritage as a means of forming a global narrative, in which the country is seen as a carrier of universal values: tolerance, absence of violence, wisdom, and peaceful coexistence. The role of the Indian diaspora, especially in the West and the Persian Gulf, is also seen as an important mediator in the transmission of cultural codes and values. The diaspora acts not only as a cultural repeater but also as an active participant in economic, political, and educational processes, strengthening India’s influence abroad. In addition, problems related to the fragmentation of diaspora communities, the politicization of identity, and social inequality were also noted. In conclusion, the author comes to the conclusion that Indian "soft power" is a complex and multifaceted phenomenon that combines cultural, historical, and political elements, as a result of which India strengthens its position in the global competition for the consciousness and sympathy of the international community.